2012
DOI: 10.1148/radiol.11110821
|View full text |Cite
|
Sign up to set email alerts
|

Articular Cartilage: In Vivo Diffusion-Tensor Imaging

Abstract: In vivo DT imaging of patellar cartilage is feasible, has good test-retest reproducibility, and may be accurate in discriminating healthy subjects from subjects with OA. ADC and FA are two promising biomarkers for early OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 41 publications
7
91
0
Order By: Relevance
“…Although diffusion imaging may supplement other quantitative techniques for evaluating cartilage, clinical studies that use the technique are rare. However, in 1 study, diffusion tensor imaging showed excellent reproducibility and may be able to differentiate healthy from OA subjects 19 . Clinical studies examining the potential role of gagCEST in the assessment of OA-related cartilage degeneration are lacking.…”
Section: Rheumatologymentioning
confidence: 87%
“…Although diffusion imaging may supplement other quantitative techniques for evaluating cartilage, clinical studies that use the technique are rare. However, in 1 study, diffusion tensor imaging showed excellent reproducibility and may be able to differentiate healthy from OA subjects 19 . Clinical studies examining the potential role of gagCEST in the assessment of OA-related cartilage degeneration are lacking.…”
Section: Rheumatologymentioning
confidence: 87%
“…DTI parameters MD and FA provide an exquisite and useful tool for non-invasive and intravoxel investigation of human tissue microstructures [27][28][29]. However, the application of DTI to the cancellous bone is not completely straightforward, as diffusion MRI in this area is hampered by the need for fat suppression, high b values and by the scarce amount of water with a subsequent low signal [45].…”
Section: Discussionmentioning
confidence: 99%
“…From DTI measurements, it is possible to derive the mean diffusivity (MD) of water in tissues and various measures of its diffusion anisotropy, such as the fractional anisotropy (FA). DTI has been extensively used to study the structure of ordered biological tissue [27][28][29]. In this work, we hypothesized that MD may be sensitive to the mean pore size increase in cancellous bone and that FA may be sensitive to variations of trabecular network anisotropy which occur with the onset of the osteoporotic disease.…”
Section: Introductionmentioning
confidence: 99%
“…DTI parameters of ADC of water in the bone marrow can be quantified, which provides a useful tool for the noninvasive investigation of human tissues (36,37). ADC values reflect the association between the direction of the diffusion of water molecules and the organizational structure (38).…”
Section: A B C a B Cmentioning
confidence: 99%